Kearifan Tempatan dalam Pendidikan Kanak-Kanak: Sorotan Terhadap Garis Panduan Hukuman Rotan di Kementerian Pendidikan Malaysia (KPM): Local Wisdom in Children Education: A Review of The Practice of Whipping Punishment in Ministry of Education Malaysia (MOE) - Ahmad Khairudin, Siti Amalina; Abdul Khalil, Shahidra; Narowi, Mumtazah (Jurnal Fiqh, 2019)
Whipping is a punishment method commonly practiced in educating that is deeply rooted in the Malaysian society. However, there are inclinations on banning this educational punishment on children, for example as in Article 29 of the Children Rights Convention. The objective of this paper is to review the historical practice of educational whipping punishment in Malaysia while making use of local wisdom in finding a middle ground of practicing whipping in schools. Hence, a qualitative method was adopted in this research by referring to primary sources from the Malaysian Education Ministry and to secondary sources such as academic articles. The data collected was analysed using thematic and descriptive approaches. The findings indicate that the objectives, as commented by the Committee of the Rights of Children in 2001, was not fully accepted. This shows that the element of local wisdom in balancing the punishment practice and the guidelines are also constructed in line with Islamic Legislation.